Regenerative braking of electric vehicle using a modified direct torque control and adaptive control theory. (July 2018) - Geraee, Shiva; Mohammadbagherpoor, Hamed; Shafiei, Mehdi; Valizadeh, Majid; Montazeri, Farshad; Feyzi, Mohammad Reza
Abstract: This paper represents a novel regenerative braking approach for electric vehicles. The proposed method solves the short-range problem which is related to the battery discharge. The direct torque control switching algorithm is modified to recover electrical energy from electric vehicle, driven by brushless direct-current motor, without using the additional power converter or the other electrical energy storage devices. During regenerative braking process, a switching pattern is applied to the inverter which is different from the normal operation due to the special arrangement of voltage vectors. The new switching pattern is considered to convert mechanical energy into electrical energy. State of charge of the battery is used as a performance indicator of the proposed method. Simultaneously, a model reference adaptive system is designed to tune the system's parameters. Several simulations are conducted to validate the performance and effectiveness of the proposed methods. The results show the high capability of designed methods.